Thematic Interpretation of Student Management in Educational Institutions - Asep Irfan Fanani (Indonesian Journal of Islamic Education, 2023)
The process of interpreting the Qur'an by collecting verses that have the same purpose and meaning in discussing a theme, arranging them according to the time it is derived by examining the causes of their derivation, and then providing explanations, descriptions, comments, and the main content of the sentence is the meaning of "thematic interpretation" (maudhu'i). The purpose of this literature review is to determine the theme (maudhu'i) of the topic of student management in Islamic educational institutions. This study employs a qualitative descriptive method for data collection and is informed by literature reviews. The study's findings present the verses discussed and analyzed in student management. The meaning of student management is explained from the perspective of the QS Al-Kahfi verses 23-24 and 69, QS Al-Hasyr verse 18, and QS Az-Zumar verse 29. They stated that each management student process must be appropriately planned, organized, carried out, and supervised.